Outcomes of the Uniportal Video-Assisted Thoracoscopic Surgery in the Treatment of Pleural Empyema- An Innovative and Less Invasive Thoracoscopic Approach - Niaz Hussain; Nuvair Zia; Mudasir Ibal dar (Annals of Abbasi Shaheed Hospital and Karachi Medical & Dental College, 2023)
Objective: To determine the postoperative outcomes of video-assisted thoracoscopic single port surgery (VATS) in the treatment of pleural empyema. Methods: This case series was conducted at Department of thoracic Surgery, Karachi. It was 16 months study from September 2020 to January 2022. Total 170 patients of both genders were included. Informed and written consent was taken from all included patients. Complete history and thorough clinical examination of patients were obtained. All operations were employing one lung ventilation, general anesthesia, and a double-lumen endotracheal tube. Each and every patient was followed up till 4 weeks to assess the postoperative outcomes. Data was compiled and analyzed using SPSS-21. Results: In this study mean age was 56.9±17.7 years. Out of 170 patients, 97 (57%) were male and 73 (43%) female. The postoperative outcomes of U-VATS in the treatment of pleural empyema were determined, mean operation time was 130.0±64.6minutes, mean pain score at first post-operative day was 2 ± 1.6, the mean duration of pain was 2.5±2.1 days, mean pain score after removal of chest tube was 0.33±0.9 and mean cosmetic score was 2.45±0.4. Postoperative paresthesia was observed in 9 (5.3%) cases, no wound infection was observed and satisfactory re-expansion of lung was noted in 154 (90.5%) cases. Conclusion: Even in stages 1 and 2 of the condition, pleural empyema can be effectively treated with U-VATS, and the procedure has relevant postoperative outcomes in terms of reduced discomfort, less complications, and aesthetic improvements.